Analisa Kenyamanan Pada Kendaraan Multiguna Pedesaan Dengan Pemodelan 8 Dof - Nanda Pranandita (Manutech : Jurnal Teknologi Manufaktur, 2016)
Vehicle suspension system is an important part to minimize the vibration of the vehicle caused by road unevenness. Ideal conditions would be difficult to obtain, especially in rural areas with uneven road conditions. Analysis of passive suspension system in this study is expected to explain the level of comfort in riding Rural Multipurpose Vehicles. Full car modelling with 1 DOF riders used in this study, simulated using numerical simulation software. Excitation roads used in the form of a sinusoidal wave with an amplitude of 0.05 m and a wavelength of 0.5 m. Analysis carried out on the comfort of the vertical acceleration response received driver’s head. Based on the simulation results showed that by using a constant speed between 20-40 km / h, the vehicle will be comfortable driving for more than 2.5 hours.